AGRICULTURAL LAND SUPPORT FOR FOOD IN GROGOL IN 2018 - Nurlia Miftakhul Khasanah; Agus Sudargono; Muh. Husyain Rifai (Universitas Veteran Bangun Nusantara, 2021)
Research on the carrying capacity of agricultural land for food is very important to do to determine the extent of the ability of the land to support the fulfillment of food needs of the population in an area. One of the problems in Grogol Subdistrict, Sukoharjo Regency is the tendency of land conversion that does not pay attention to production land for agriculture in order to meet the food needs of the population. This research includes 1 district which consists of 14 villages. The data used is secondary data taken from the Central Bureau of Statistics and the Agriculture Office of Sukoharjo Regency. The method used to determine the level of carrying capacity of agricultural land for food crops with the combined concept of the theory of Odum, Cristeiler, E Howard and Issard. The results showed that overall based on data in 2018 the carrying capacity of agricultural land for food in Grogol District was still low. This shows that the Grogol District area has not been able to be self-sufficient in food and has not been able to provide a decent life for its residents. Therefore, it is necessary to make certain efforts to increase the carrying capacity of food agriculture land in this area, for example by involving the population and utilizing the remaining vacant land.